DAMPAK PEMBELAJARAN BERDIFERENSIASI TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Agusta, Ratu Meri; Hardianti, Asti; Komalasari, Rena; Dewi, Ratna Sari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the impact of differentiated instruction on elementary students' motivation and academic achievement through a literature review. The analysis of various studies shows that differentiated instruction, which accommodates individual student differences, has a significant positive impact on students' intrinsic motivation, academic achievement, and engagement in the learning process. This approach is effective because it provides flexibility in choosing tasks and learning strategies, and creates an inclusive and supportive learning environment. The findings have important implications for educators to adopt differentiated instruction strategies in their teaching practices, as well as for policymakers to promote the implementation of this approach at all levels of education.